Advances in the Treatment of Neutropenia - Dale, David C. (2009)
PURPOSE OF REVIEW: This review updates treatment of neutropenia from articles published from January 2008 through April 2009. RECENT FINDINGS: Chemotherapy-induced neutropenia occurs most commonly in the first cycle of treatment. Older patients, patients with multiple co-morbidities, and those receiving more myelotoxic drugs are prone to develop neutropenia and its complications. Current guidelines recommend use of the myeloid growth factors for the first cycle of chemotherapy for patients with more that a 20 % risk of febrile neutropenia. Meta-analysis from randomized trials shows that granulocyte colony-stimulating factor (G-CSF) prophylaxis is associated with patients receiving more intensive chemotherapy, having better survival, but also having a higher risk of secondary AML. Antibiotic remain the mainstay of treatment of febrile neutropenia and are increasingly used for prophylaxis in “low risk” patients. Diagnosis and treatment of other type of neutropenia is also steadily improving. SUMMARY: The myeloid growth factor G-CSF has radically changed our approach to the management of neutropenia. Antibiotics remain the mainstay of treatment of febrile neutropenia.